2013
DOI: 10.1080/19768354.2013.768295
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of ecological trophic structures on chemical gradients in lotic ecosystems and their relations to stream ecosystem health

Abstract: The objectives of this study were to evaluate how chemical gradients and physical habitats influence trophic dynamics and chemical tolerance in relation to ecological health, based on biological integrity model in the absence of cascading pressures (cascading theory) as a control mechanism of aquatic ecosystems. We conducted physical, chemical, and biological surveys from 76 national streams and rivers of four major watersheds during 2004Á2005 along with surveys of 80 reference streams. Maximum species richnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In other words, the N:P ratios determined the sestonic CHL, which was associated with the food chain at higher trophic levels. Fish trophic compositions and tolerance guilds (14 [8]) were closely associated with the food chain and were directly affected by N:P ratios in ambient water, resulting in a modification of stream ecosystem health (based on the IBI multi-metric model, 14 [8]). Overall, the N:P ratio may be a good surrogate variable of ambient concentrations of N or P in assessing trophic linkage and diagnosing the ecological stream health in aquatic ecosystem.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In other words, the N:P ratios determined the sestonic CHL, which was associated with the food chain at higher trophic levels. Fish trophic compositions and tolerance guilds (14 [8]) were closely associated with the food chain and were directly affected by N:P ratios in ambient water, resulting in a modification of stream ecosystem health (based on the IBI multi-metric model, 14 [8]). Overall, the N:P ratio may be a good surrogate variable of ambient concentrations of N or P in assessing trophic linkage and diagnosing the ecological stream health in aquatic ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Strong negative regression coefficients (R 2 = 0.64, p < 0.001) for the N:P ratios on TP were found in numerous lentic ecosystems [22,57]. These studies indicated that the N:P ratio is a key regulator of the nutrient regime, and of primary production, in ambient water [11,12,58], and is also a major indicator of ecological river health in multi-metric fish models [8]. Our results indicate that the N:P ratios in forest region (high N:P) were clearly segregated from the WTPs region (low N:P), but partial overlaps in the N:P ratios were also shown in the cropland and urban regions.…”
Section: Effect Of Mass Ratios Of N:p On Nutrient Regimes and Their Imentioning
confidence: 99%
See 3 more Smart Citations